CONCEPTUAL PRINCIPLES OF BUDGET DECENTRALIZATION STRATEGY DEVELOPMENT IN UKRAINE - CHIMSHIT, Sergey; GOLOVKOVA, Liudmila; GRABOVSKII, Ihor; YAKYMOVA, Alla (Journal of European Economy, 2020)
The main strategic task of modernizing the system of public administration and territorial structure of power should be the creation of effective local selfgovernment, creating comfortable living conditions for citizens, providing them with high quality and affordable public services. Economically active businesses, a sufficient number of skilled workers, developed industrial and social infrastructure are the basis for successful community development. The society still lacks effective financial mechanisms to motivate local governments to the effectiveness of decisions on socio-economic territorial development. Given this, the article analyses the current financial problems of decentralization in Ukraine, the impact of national economic development and budget policy on the financial capabilities of local governments. Conceptual directions and resources for increasing the financial independence of the regions have been identified. It is established that the main result of the budget decentralization reform should be not so much more efficient allocation and redistribution of community financial resources, as greater interest and capacity of local governments to increase local budget revenues, find reserves, and improve the efficiency of tax administration and fees. Local self-governments must make decisions based on the following cause-andeffect relationship: the availability of sufficient resources in local budgets is a consequence of the level of economic activity in the region. JEL: E440, E690, H610, Н710 (770).